Implementasi Program Pemberdayaan Masyarakat Pesisir Di Kabupaten Takalar Pada Dinas Perikanan Provinsi Sulawesi Selatan - Muhammad Natsir Mallawi; Alfiana Akbar (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
This research aims to find out how the coastal community empowerment program is implemented in Takalar Regency at the South Sulawesi provincial fisheries service. What factors support and inhibit the implementation of the coastal community empowerment program in Takalar Regency at the South Sulawesi provincial fisheries service. The type of research used is a qualitative descriptive approach. The focus of this research is increasing capacity, providing access to technology and information, capital, infrastructure, market guarantees, productive economic assets. The number of informants was 10 employees of the South Sulawesi provincial fisheries service. The data collection techniques used were observation, interviews, documentation, liberal research. The data analysis technique used is data reduction, which means summarizing important things. The data presentation carried out in this research is the data obtained through research results are presented and presented in text or written form and described in qualitative form. The results of this research show that the programs provided by the fisheries service to coastal communities in Takalar Regency are appropriate and there has been improvement, namely the existence of activity programs from the government and the South Sulawesi provincial fisheries service so that with these programs and activities coastal communities are able to empower themselves.